0587 The Effect of Continuous Positive Airway Pressure (CPAP) on Health Related Quality of Life (HRQOL) as measured by Quality of Well being self Administered questionnaire (QWB-SA). (27th April 2018) - batool-Anwar, S; Quan, S
Abstract: Introduction: To examine the effect of continuous positive airway pressure (CPAP) on Health-related quality of life (HRQoL) as measured by the Quality of Well Being Self -Administered questionnaire (QWB-SA) among patients with Obstructive Sleep Apnea (OSA). Methods: Participants from The Apnea Positive Pressure Long-term Efficacy Study (APPLES) were included in this analysis. APPLES was a 6-month multicenter randomized, double-blinded intention to treat study. The participants with an apnea hypopnea index &gt 10 events/hour initially randomized to CPAP or Sham group were asked to complete QWB-SA questionnaire at baseline, 2, 4 and 6 month visits. QWB-SA is one of the few instruments that can help calculate Quality Adjusted life years (QALYs) as an expression of health outcome. Items assessing chronic symptoms, physical symptoms, and mental health are included in QWB-SA questionnaire. Results: There were no group differences in age, AHI, BMI, ESS, or gender between the CPAP and Sham groups. Mean age, AHI, BMI, and Epworth Sleepiness Score (ESS) were 50 ± 13 [SD] years, 40 ± 25 /hr, 32.0 ± 7.1 kg/m2 and 10.0 ± 4.4 respectively. QWB-SA scores were available at baseline, and 2, 4 & 6 months after treatment in CPAP ( n 556) and Sham CPAP ( n 546) groups. There were no significant differences in QWB scores among mild, moderate or severe OSA participants at baseline. Similarly, when examined at 2, 4 and 6- month intervals the QWB scores were not different between the CPAP and Sham groups. Stratifying the groups by gender and PAP adherence also did not materially change the results. Conclusion: Although a valuable instrument for assessing HRQoL and treatment response for a variety of chronic illnesses, and in contrast to other sleep specific QoL measures, this study did not detect any change in QWB after initiation of CPAP. In addition, the severity of OSA did not have an impact on QWB even after CPAP treatment. Support (If Any): APPLES was funded by HL68080 from the National Heart, Lung and Blood Institute.